2022
DOI: 10.1097/pec.0000000000002779
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Fentanyl to Reduce Pain and Improve Oral Intake in the Management of Children With Painful Infectious Mouth Lesions

Abstract: Objectives: Painful infectious mouth conditions such as herpangina, hand-foot-and-mouth disease, and herpetic gingivostomatitis can cause pain, dehydration, and hospitalization in young children. Treatment for these conditions is generally supportive and directed toward pain relief from ulcerative lesions, thus facilitating oral intake, and preventing dehydration. Attempts at oral therapy at home and in the emergency department are often refused and immediately spit back out. This study evaluated the efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Out of 23 studies included, 18 studies were conducted in children: 1 PS in the PHES (Murphy et al, 2017 [ 38 ]), 9 observational studies (Akinsola et al, 2018 [ 39 ], Anderson et al, 2022 [ 40 ], Cole et al, 2009 [ 41 ], Crelin et al, 2010 [ 42 ], Finn et al, 2010 [ 43 ], Kelly et al, 2018 [ 44 ], Nemeth et al, 2019 [ 45 ], Saunders et al, 2010 [ 46 ], Schaefer et al, 2015 [ 47 ]) and 8 RCTs (Borland et al, 2011 [ 48 ], Fein et al, 2017 [ 49 ], Frey et al, 2019 [ 50 ], Graudins et al, 2015 [ 51 ], Quinn et al, 2021 [ 52 ], Reynolds et al, 2017 [ 53 ], Ruffin et al, 2022 [ 54 ], Younge et al, 1999 [ 30 ]) in the ED; 5 studies were conducted in the adult population: 1 observational study in the PHES setting (Tanguay et al, 2020 [ 55 ]), 2 observational studies (Assad et al, 2023 [ 56 ], Belkouch et al, 2015 [ 57 ]) and 2 RCTs (Nasr Isfahani et al, 2022 [ 58 ], Nazemian et al, 2020 [ 59 ]) in the ED setting; one subgroup analysis of an observational study reported data on the elderly patients in the PHES (Tanguay et al, 2020 [ 55 ]). A total of 10,280 patients were included: 1203 in the PHES setting (94 children, 729 adults and 380 elderly) and 9077 in the ED setting (8714 children and 363 adults).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of 23 studies included, 18 studies were conducted in children: 1 PS in the PHES (Murphy et al, 2017 [ 38 ]), 9 observational studies (Akinsola et al, 2018 [ 39 ], Anderson et al, 2022 [ 40 ], Cole et al, 2009 [ 41 ], Crelin et al, 2010 [ 42 ], Finn et al, 2010 [ 43 ], Kelly et al, 2018 [ 44 ], Nemeth et al, 2019 [ 45 ], Saunders et al, 2010 [ 46 ], Schaefer et al, 2015 [ 47 ]) and 8 RCTs (Borland et al, 2011 [ 48 ], Fein et al, 2017 [ 49 ], Frey et al, 2019 [ 50 ], Graudins et al, 2015 [ 51 ], Quinn et al, 2021 [ 52 ], Reynolds et al, 2017 [ 53 ], Ruffin et al, 2022 [ 54 ], Younge et al, 1999 [ 30 ]) in the ED; 5 studies were conducted in the adult population: 1 observational study in the PHES setting (Tanguay et al, 2020 [ 55 ]), 2 observational studies (Assad et al, 2023 [ 56 ], Belkouch et al, 2015 [ 57 ]) and 2 RCTs (Nasr Isfahani et al, 2022 [ 58 ], Nazemian et al, 2020 [ 59 ]) in the ED setting; one subgroup analysis of an observational study reported data on the elderly patients in the PHES (Tanguay et al, 2020 [ 55 ]). A total of 10,280 patients were included: 1203 in the PHES setting (94 children, 729 adults and 380 elderly) and 9077 in the ED setting (8714 children and 363 adults).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported INF to be effective in reducing pain at different time points (Cole et al, 2009 at 10 and 30 min [ 41 ]; Crellin et al, 2010 [ 42 ]; Finn et al, [ 43 ] at 5 and 30 min; Saunders et al, 10, 20 and 30 min [ 46 ]). Two studies [ 44 , 45 ] and six RCTs reported INF to be equally effective as comparators [ 48 , 50 , 51 , 52 , 53 , 54 ]. Two RCTs demonstrated INF to be more effective in reducing pain: Fein et al, 2017, compared INF to the “standard of care” (more effective at 20 min after administration, no differences at 10 and 30 min) [ 49 ] and Younge et al, 1999, compared IM 0.2 mg/kg morphine (more effective at 10 min, no difference at 20 and 30 min) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations